Elliot's Arctic Surprise - Barr, Catherine (Great Biritan Frances Lincoln Children's Books, 2015)
A great picture story book with an environmental message, developed in conversation with Greenpeace UK. When one little boy discovers a message from Father Christmas asking for help to save his home from the oil drillers, he hitches a lift from a kind old sailor and together with children from around the world, they set sail to confront the oil men. Elliot desperately wants to save the Arctic and stop Christmas being cancelled, but will the oil drillers back down and what is the old sailor's big surprise...?